Communication and Social Preferences: An Experimental Analysis - Antonio Gabrales; Francesco Feri; Piero Gottardi; Miguel A. Meléndez-Jiménez (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper reports on experiments regarding cheap talk games where senders attempt deception when their interests are not in conflict with those of the receiver. The amount of miscommunication is higher than in previous experimental findings on cheap talk games in situations where senders' and receivers' interests are not in conflict. We obtain this even though, as in previous literature, some participants appear to feature a cost of lying. We argue our findings could be attributed to distributional preferences of senders who lie to avoid the receiver getting a higher payoff than herself.
Keywords: D83; C72; G14; 330; experiments; cheap talk; deception; conflicts of interest; social preferences